PEMBELAJARAN MATEMATIKA BERBASIS KEARIFAN LOKAL GUSJIGANG KUDUS PADA SISWA SLOW LEARNER - savitri wanabuliandari; Jayanti Putri Purwaningrum (EduMa: Mathematics education learning and teaching, 2018)
Slow learner have difficulties in mathematics subjects so it is necessary to develop math module based on local wisdom Gusjigang Kudus. The purpose of this research is to know the result of questionnaire of Â slow learner need to develop the module of math based on local wisdom, andÂ  result of interview with teacher. The type of research is qualitative. The subject is the teacher and the slow learner in SD 1 Muhammadiyah Kudus. Techniques of data collection using questionnaires, interviews, and documentation. Based on the results of the questionnaire analysis, the needs of slow learner concluded that slow learner need a mathematical module that can help understand the material, help solve daily problems, and take advantage of local wisdom in the area. Based on the teacher interviews, the module that can help slow learner does not exist yet, and the books in the schools do not emphasize issues related to local wisdom.